Choriocarcinoma with atypical presentations causing diagnostic dilemma - Paudyal, Pooja; Rawal, Suniti; Katuwal, Neeta; Rajbhandary, Sanyukta; Kunwar, Asma (Journal of Kathmandu Medical College, 2022)
Even though choriocarcinoma commonly present with abnormal uterine bleeding and pelvic mass, various unusual and atypical presentations of choriocarcinoma have been reported which cause diagnostic dilemmas. Here we present two such cases with unusual presentations of choriocarcinoma- one with pulmonary embolism and another with vulvovaginal mass.